Use of local anesthesia in ear surgery: technique, modifications, advantages, and limitations over 30 years’ experience - Mohamed A. El-Begermy; Marwa M. El-Begermy; Amr N. Rabie; Abdelrahman E. M. Ezzat; Ahmed A. Kader Sheesh (The Egyptian Journal of Otolaryngology, 2016)
En Abstract Background Local anesthesia (LA) is safe and well established for a variety of ear operations. It has many advantages compared with general anesthesia (GA). Objective This article is intended to be a comprehensive reference for those who use this art, in which we have more than 30 years of experience. We also aimed to find out the effect of LA on blood pressure (BP) and heart rate (HR), operative time, time of anesthesia with different adrenaline concentrations, and patient satisfaction with LA. Patients and methods This was a retrospective study of our experience in the technique of LA in more than 2600 patients spanning more than 30 years, along with modifications introduced. Additional prospective trials were also conducted. BP and HR were monitored during LA injection in 200 patients. The calculated operative time was compared between two groups of 21 patients each: the first group was operated upon under LA and the other under GA. Anesthesia time was calculated for LA with different adrenaline concentrations (1: 20 000–1: 200 000 and 0% or no adrenaline) by means of injections over both the mastoid and the forearm on five volunteers. Patient satisfaction was measured using postoperative questionnaire in 200 patients. Results Patients showed initial increase in BP due to apprehension, which was abolished with diazepam; a second increase in BP and HR occurred after LA injection by 3–10 min. LA statistically significantly shortened the operative time compared with GA. Time of anesthesia was longer using anesthetic solution with higher adrenaline concentration and was longer on the mastoid as compared with the forearm. Finally, 92% of the patients showed satisfaction from the procedure. Conclusion LA is a safe and effective way of anesthesia in ear surgery, allowing intraoperative testing of hearing, facial nerve action, and eustachian tube patency. With high adrenaline concentration, it allows excellent hemostasis, shortens the operative time, and increases the time of anesthesia, allowing probable prolonged postoperative analgesia and is well tolerated by the patients.